Nep 2020 Curriculum Reform And Pedagogical Innovations In Higher Education (Journal of Namibian Studies : History Politics Culture, 2023)
The National Education Policy (NEP) 2020 in India represents a significant shift in the approach to higher education, emphasizing curriculum reform and pedagogical innovations to meet the evolving needs of learners and society. This literature review and conceptual analysis explore the implications of NEP 2020 on curriculum development and pedagogy in higher education. Drawing upon theoretical frameworks in curriculum studies and pedagogy, the paper examines key changes introduced by NEP 2020 and reviews existing literature on curriculum reform and pedagogical innovations in higher education, both within the Indian context and globally. Through a synthesis of literature, the paper identifies common themes, emerging trends, and challenges in curriculum reform and pedagogy. Methodologically, the paper adopts a qualitative research approach, utilizing data collection methods such as literature review and conceptual analysis. The conceptual analysis section examines NEP 2020 in action through case studies of institutions implementing reforms, highlighting both successes and challenges. The paper concludes with a discussion of the implications for higher education policy and practice, recommendations for future research, and reflections on the impact of NEP 2020 on curriculum and pedagogy in Indian higher education.